Layer by layer TiO2 thin films and photodegradation of Congo red - Sansiviero, Maria T. C.; dos Santos, David S.; Job, Aldo Eloizo [UNESP]; Aroca, Ricardo F. (Elsevier B.V. Sa, 2011)
Layer by layer (LbL) self-assembled technique was used to fabricate TiO2 films onto glass and quartz slides. The LbL sequence was PAH/PSS/TiO2(PSS/TiO2)(5) (PSS = poly(sodium-4-styrene sulfonate), PAH = poly(allylamine hydrocloride)). These LbL thin films were characterized by Raman spectroscopy. The Raman spectrum confirmed the formation of TiO2 nanoparticles in the anatase phase which average size of the particles around 30 nm and thickness of the film estimated around 40 nm as determined by atomic force microscopy (AFM). The photodegradation of Congo red (CR) dye immobilized over the LbL film was studied. Reference resonance Raman scattering (RRS) and Raman scattering (RS) spectra of Congo red were recorded with the 514.5 nm and 785 nm excitation laser lines. The photodegradation experiments were carried out by exposing the LbL TiO2 film/CR to UV radiation in a container with distilled water. After UV exposure, degradation products were monitored by Raman spectroscopy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TiO2; LbL film; Congo red; Photocatalysis; Resonance Raman scattering